ANALISIS HUKUM TERHADAP PENGELOLAAN TEMPAT PEMBUANGAN AKHIR (TPA) BANTARGEBANG DALAM PERSPEKTIF HAK WARGA SEKITAR ATAS LINGKUNGAN SEHAT - Sandy Alun Samudra MB; Ujang Supian; Ikhwan Aulia Fatahillah (Journal of Indonesian Comparative of Syari'ah Law, 2025)
This paper aims to determine the impact of the Bantargebang Final Disposal Site (TPA) on the surrounding environment and to examine its laws and regulations in order to assess the extent to which the management of the Bantargebang TPA has fulfilled the legal provisions related to the rights of citizens to a healthy environment. The method used in this study is the normative legal research approach. The results of the study found that there had been a violation of Article 28H paragraph (1) of the 1945 Constitution and Article 65 paragraphs (1) and (2) of the PPLH Law against the rights of citizens to a good and healthy environment, with evidence that the management of the Bantargebang TPA has not been optimal due to pollution of water, air, and soil that has had an impact on the surrounding community for years. In fact, human rights guidelines should be met because a decent standard of living and continuous improvement in living conditions have been guaranteed by the state. Legally, the state and local governments have failed to guarantee the quality of a healthy environment around the Bantargebang TPA because they are considered less capable of preventing the impacts of waste management at the TPA, this can be categorized as a form of violation of the right to a healthy environment.